La formation des mots dérivés et flexionnels dans l’anthologie poésie de Couleur Femme : une étude morphologique - Munawaroh Ainur Rosit, Saidatina; Oktavia Dwi Astuti, Dies (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2025)
This research aims to determine the types of derivative word formation and inflectional word formation found in the poetry collection “Couleur Femme” and determine the dominant types of word formation. This research uses a qualitative descriptive research method. The data source for this research is poetry by Pranita Dewi in the bilingual poetry collection “Couleur Femme.” The poems by Pranita Dewi which are the source of research data are “Ambarawa, vile sans personne; Edge Park; Melka, la mariée d’une saison; and Je commence cette année avec toux et asthma”. The data for this research are words that have derivative and inflectional word formation in the four poems. The research results show eight types of derivative word formation: prefixation, suffixes forming nouns, adjectives forming adjectives, adverbs forming adverbs, verbs forming verbs, zero derivations, popular compositions, and absorption. Furthermore, there are five types of inflectional word formation: conjugation, flexion of masculine nouns to become feminine, flexion of singular nouns to become plural general nouns, flexion of singular adjectives to plural, and flexion of masculine adjectives to feminine. The dominant type of derivative word formation is verb-forming suffixes. The dominant inflectional kind of word formation is conjugation.